Georgia's Post-Independence Scientific Output and Prospects - Chagelishvili, Ana; Mushkudiani, Zurab (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
After the collapse of the USSR and the gaining of independence, the breaking of the informationally limited space led Georgia to the need to adopt new goals, policies, or reforms in the field of science, which should bring Georgia closer to the international scientific community. The purpose of the article is to study the evolution of Georgia's scien-tific output after gaining independence and analyse the prospects of development. To achieve the set goal, a systematic methodological approach is used: desk research, induction, deduction, statistical, time and space comparison, analysis, synthesis, etc. The paper dis-cusses as separate directions the historical background; The institu-tional landscape and the role of leading scientific institutions; The challenges of Georgian scientific journals and the issue of indexing in international scientific databases; Scientific publication activity; The number and structure of Georgian researchers; Involvement of the state in the formation of the scientific landscape; Expenditure on re-search and development; Scientific cooperation. The study showed that since independence, the scientific sector of Georgia has encoun-tered two major issues: financial constraints and the outflow of scien-tists from the country. Yet, the scientific situation has slightly im-proved, although the number of scientists is still not high. In recent years, the number and quality of scientific articles have increased, especially in medicine and engineering. In the future, for increasing scientific productivity, Georgia can increase research funds, promote holding talented scientists, and improve cooperation with interna-tional bodies. Creating programs for innovation and strengthening patent mechanisms will also be an input into technological progress.